Psychological Capital and Employee Well-Being: Systematic Insights - Kaur, Achint; Goel, Manisha; Sindwani, Rajiv (Journal of Economics and Management, 2026)
The review synthesizes research on employees’ psychological capital and its relationship with employee well-being. The aim is to critically evaluate the literature which examines how positive psychological resources mitigate workplace deviance and enhance employee well-being. It clarifies dominant theoretical explanations, resolves inconsistencies in causal positioning, and identifies key research gaps, drawing primarily on Conservation of Resources theory, Social Exchange theory, and the Job Demands–Resources framework to explicate the conceptual positioning of psychological capital. The potential of psychological capital as a key mechanism for sustaining resources, even in a challenging organizational climate. The organizations enhance employee well-being by embedding psychological capital development interventions within HR practices, leadership approaches, and supportive work climates. Adverse workplace conditions often give rise to undesirable attitudes and behaviours such as cynicism, turnover intentions, job stress, anxiety and deviance. This enables the organisation to adopt a proactive strategy for promoting employee well-being.